2016
DOI: 10.1515/zireb-2016-0013
|View full text |Cite
|
Sign up to set email alerts
|

When Employers Betray: A Study of Psychological Contract Breach Among Croatian Employees

Abstract: Abstract:In this paper we report the results of a study exploring psychological contract breach (PCB) in a heterogeneous sample of Croatian employees (N=363). In addition to reporting PCB, the participants informed us about their basic demographic characteristics, job attitudes (job satisfaction and organizational commitment) and reported three aspects of their job performance (in-role performance, organizational citizenship behavior, counterproductive work behavior). Our analyses showed that PCB experience de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…Furthermore, psychological contract breach states that employees notice an inconsistency between what they were assured by the organization and what they have received. Thus, it is reported that when individuals are perceived a high level of psychological contract breach, they sense irritability and require a need to reinstate the unfair condition, for example, dedicating less struggle to lower their costs or maybe taking the property from the organization to raise its budget 72 . In the end, this leads to counterproductive work behavior.…”
Section: Theory and Hypotheses Developmentmentioning
confidence: 99%
“…Furthermore, psychological contract breach states that employees notice an inconsistency between what they were assured by the organization and what they have received. Thus, it is reported that when individuals are perceived a high level of psychological contract breach, they sense irritability and require a need to reinstate the unfair condition, for example, dedicating less struggle to lower their costs or maybe taking the property from the organization to raise its budget 72 . In the end, this leads to counterproductive work behavior.…”
Section: Theory and Hypotheses Developmentmentioning
confidence: 99%
“…Most studies on the relationship between PCB and organizational commitment have focused on affective commitment, with evidence suggesting that PCB is associated with decreased commitment (e.g., Antonaki and Trivellas, 2014;Gali c et al, 2016;Zhao et al, 2007). Few studies have examined PCB in relation to the three dimensions of organizational commitment with results showing diverse influences of PCB on the dimensions of commitment.…”
Section: Introductionmentioning
confidence: 99%
“…psihološkog ugovora. Galić, Tonković Grabovac, Gotvald i Jerneić (2016) su ustanovili da je doživljaj kršenja ovisan o dobi, stažu i obrazovanju, a njegove posljedice su smanjeno zadovoljstvo i zalaganje u radu. Dautović i Galić (2016) su dodatno istraživali generacijske razlike: mlađa kohorta (tzv.…”
Section: Psihosocijalni Aspekti Rada U Vrijeme Društvenih Promjenaunclassified